Empirical Study Using Analysis Techniques Pathways for RM Bumi Aki Employees in Bogor City and Surroundings - Ahmad Zulfikar; Widodo Sunaryo; Hari Muharam (International Journal of Management Research and Economics, 2024)
This study examines the influence of servant leadership style and personality traits on employee performance through the mediation of work motivation at Bumi Aki Restaurant in Bogor City. A quantitative approach using path analysis technique was employed on a randomly selected sample of Bumi Aki Restaurant employees. The results indicate that both servant leadership style and personality traits have a significant positive effect on work motivation, and work motivation mediates the relationship between these variables and employee performance. The implications highlight the importance of developing servant leadership style and positive personality traits to enhance employee performance, providing insights for human resource management in the restaurant industry, and suggesting avenues for further research to deepen the understanding of these dynamics.